2023
DOI: 10.1002/smll.202304321
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Self‐Adaptive Multi‐Response Thermochromic Hydrogel for Energy‐Saving Smart Windows and Wearable Temperature‐Sensing

Long Xie,
Xuechuan Wang,
Xiaoliang Zou
et al.

Abstract: Buildings account for ≈40% of the total energy consumption. In addition, it is challenging to control the indoor temperature in extreme weather. Therefore, energy‐saving smart windows with light regulation have gained increasing attention. However, most emerging base materials for smart windows have disadvantages, including low transparency at low temperatures, ultra‐high phase transition temperature, and scarce applications. Herein, a self‐adaptive multi‐response thermochromic hydrogel (PHC‐Gel) with dual tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 68 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Particularly, smart gels that can change their optical properties (e.g., fluorescence, structural color, and transparency) by responding to external stimuli (e.g., heat, light, chemicals, and electricity) have attracted great attention. [44][45][46] These responsive gels have become ideal candidates for generating multifunctional information handling models and have been widely used in anti-counterfeiting technology, information encryption and smart windows. [47][48][49][50][51] Interestingly, the prepared PEA-AA-MAm/ IL gel demonstrated an obvious transparency-shifting behavior under the stimulation of different polar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, smart gels that can change their optical properties (e.g., fluorescence, structural color, and transparency) by responding to external stimuli (e.g., heat, light, chemicals, and electricity) have attracted great attention. [44][45][46] These responsive gels have become ideal candidates for generating multifunctional information handling models and have been widely used in anti-counterfeiting technology, information encryption and smart windows. [47][48][49][50][51] Interestingly, the prepared PEA-AA-MAm/ IL gel demonstrated an obvious transparency-shifting behavior under the stimulation of different polar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Energy conservation and emission reduction have become a global challenge. It has been reported that the building energy consumption accounts for 40% of the total energy, of which half is consumed by heating, ventilation, and air conditioning . Therefore, improving the energy efficiency of buildings is the key to energy conservation. …”
Section: Introductionmentioning
confidence: 99%
“…Further technological advancements in these sensors have been supported by improvements in wireless communication technology, which facilitate seamless data transmission between the sensors and mobile monitoring devices. Additionally, the advancement of wearable, transparent, , and flexible electrode materials, alongside the innovation of antimicrobial and biocompatible hydrogels, , has not only maintained the essential transparency of contact lenses but also improved their functional integration, making the lenses comfortable to wear. However, only a few of the electrochemistry-based technologies developed have been commercialized, owing to the following reasons: (1) The existing electrochemical-based smart contact lenses (glucose sensors) generate heat that could damage the tissues of eyes due to the presence of a circuit.…”
Section: Introductionmentioning
confidence: 99%